Knowledge Level and ARI Prevention Efforts: A Study at Tarumajaya Public Health Center - Aditya, Muhammad Fajar; Mustafida, Ika; Juliani, Enni (Jurnal Keperawatan Profesional (KEPO), 2025)
Acute Respiratory Infection (ARI) was one of the main health problems in Indonesia and remained a significant cause of morbidity and mortality, especially among vulnerable groups. Various risk factors such as age, gender, environmental conditions, and level of public knowledge were known to influence the prevalence of this disease. This study aimed to analyze the relationship between the level of community knowledge and ARI prevention efforts in the working area of Tarumajaya Public Health Center, Bekasi Regency. This study used a quantitative approach with a cross-sectional design. A total of 85 subjects were selected using a purposive sampling method. The research instrument was a questionnaire whose validity and reliability had been tested. Data were analyzed using the Chi-square test. The results showed a significant relationship between knowledge level and ARI prevention efforts (p-value < 0,0001). Subjects with higher levels of knowledge tended to perform better preventive behaviors. These findings indicated that strategic efforts from health workers were needed to improve public awareness and knowledge through sustainable promotive and preventive programs. In conclusion, knowledge was associated with ARI preventive behavior; therefore, educational interventions played a key role in controlling this disease, especially in high-incidence areas such as the Tarumajaya Public Health Center.